Clinical and economic impact of the introduction of a nucleic acid amplification assay for Clostridium difficile - Margaret M. Guinta; Kristen Bunnell; Amanda Harrington; Susan Bleasdale; Larry Danziger; Eric Wenzler (BMC, 2017)
Abstract Background The clinical outcomes and cost implications of a diagnostic shift from an EIA- to PCR-based assay for Clostridium difficile infection (CDI) have not been completely described in the literature. Methods The impact of the PCR-based assay on the incidence and duration of CDI therapy was compared to the EIA assay for patients with a negative CDI diagnostic result. Secondary clinical and economic outcomes were also evaluated. Independent predictors of receipt of antibiotic therapy were assessed via logistic regression. Results 141 EIA and 140 PCR patients were included. Significantly more patients were started or continued on anti-CDI antibiotic therapy after a known negative assay result in the EIA group (26 patients vs. 8 patients, P = 0.002). Duration of antibiotic therapy after a known negative result was significantly shorter in the PCR group (1 vs. 4 days, P = 0.029) and a 23% reduction in the number of tests obtained per patient was observed (1.41 ± 0.86 vs. 1.82 ± 1.35, P = 0.007). The over fourfold difference in per-test cost of the EIA assay ($8.33 vs. $42.86, P < 0.0001) was offset by the overall medication costs required for the increased treatment in the EIA group ($546.60 vs. $188.96, P = 0.191). Utilization of the EIA-based CDI assay was associated with increased odds of CDI treatment after a negative test (aOR 4.71, 95% CI 1.93-11.46, P = 0.001). Conclusion The transition from an EIA to PCR-based assay for diagnosing CDI resulted in a significant decrease in the number of patients treated and the duration of treatment in response to a negative test result. This significant decrease in treatment resulted in decreased costs offsetting the utilization of a more expensive molecular test for patients with a negative CDI diagnostic result.